Optimizing the blood component production process. (14th July 2015) - Cid, J.; Velásquez, C. A.; Lozano, M.
Abstract : Background: Automation of blood component preparation (BCP) from whole blood (WB) collections can help to optimize the BCP process, and it is increasingly being widespread implemented. Aim: This review summarizes the quality of blood components obtained with new automated devices developed in the 2000s. Methods: We reviewed available literature on the quality of blood components obtained with new automated devices. Results: Blood components obtained with the new devices met European standards. Of note, compared with platelet concentrates obtained with manual methods, automation of BCP improved the consistency of the final products. Conclusion: The complete automation of BCP from WB collections is still in development, and it represents a huge change in paradigm.